English Grammar : (Video Aided Instruction, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! If your nouns, verbs, and pronouns don't agree, your reader will probably find your sentences hard to understand. That's because these parts of speech can all be affected by number (singular or plural) and gender (male or female). This unique program will help you master the "art of agreement" so your sentences will be error-free and easy to follow! So don't let mistakes in English grammar embarrass you - now you can eliminate them from your speaking and writing forever.